PENGARUH EARNING PER SHARE (EPS), DEBT TO EQUITY RATIO (DER), RETURN ON EQUITY (ROE) DAN DIVIDEND PAYOUT RATIO (DPR) TERHADAP HARGA SAHAM (STUDI PADA PERUSAHAAN INDUSTRI MANUFAKTUR YANG GO PUBLIC DI BURSA EFEK INDONESIA TAHUN 2010 - 2013) (Students' Journal of Economic and Management, 2016)
The objective of the study is to examine the effect of Earning Per Share , Debt to Equity Ratio , Return on Equity and Dividend Payout Ratio to the stock price. The research was conducted on an industrial manufacturing company that go public on the Indonesian Stock Exchange. The sampling method in this study using purposive sampling method with the study period of 2010 to 2013. The data used in this research is data from  manufacturing companies that meet the selection criteria . The analytical method used in this study is multiple regression analysis.  The multiple regression shows that EPS, ROE and DPR have positive and significant impact on stock prices, whileDER has negative and not significant effect on stock prices. Adjusted R Square is 0,901 this means 90.1% of the dependent variable can be explained by the independent variable, while the remaining 9.9 % is explained by other causes outside the model Keywords: Stock Price, Earning Per Share, Debt to Equity Ratio, Return On Equity, and Dividend Payout Ratio.